Computer simulation of overvoltages in 6–10 kV distribution networks for single-phase ground faults - K. S. Kurochka; V. I. Tokochakov; E. A. Karabchikova; K. A. Panaryn (Системный анализ и прикладная информатика)
Nowadays, when designing and operating electric power systems, special attention is paid to predicting emergency situations and minimizing losses in case they occur. The most common method of overvoltage investigations is the use of simulation models in specialized application packages, which imposes additional qualification requirements on the electrical engineer.The authors propose modeling technologies and a software tool for modeling and research of overvoltages that occur in 6–10 kV distribution networks at single-phase ground faults, including the method of visual design of the distribution network through the use of information technology and automated generation of mathematical model for its further study to analyze overvoltages.